Iguanas : Biology and Conservation. - Alberts, Allison C. (University of California Press, 2004)
In what is certain to be the key reference on iguanas for years to come, some of the world's leading experts offer a clear and accessible account of the latest research on the evolution, behavioral ecology, and conservation of these highly visible and increasingly endangered creatures, much loved by professional herpetologists and hobbyists alike. The book begins with an introduction by noted iguana biologist Dr. Gordon Burghardt that examines the state of iguana research, --past, present, and future--with an emphasis on social behavior. Three major sections follow, each opening with a synthesis by the volume editors, who survey the current status and likely future direction of investigations in the pertinent area.